Employee Wellbeing dan Kinerja Pegawai Berkelanjutan: Peran Mediasi Work Engagement - Amin Noor, Herlina; Rusli, Muh.; Komara, Nandang; Sattar, Usman; Safira Rospitasari Harun Sally, Jihan; Lestari, Sulfaedah; Syahrul, Syahrul (Jurnal Teknologi dan Bisnis Cerdas, 2025)
Changes in work patterns and increasing performance demands require organizations to focus not only on targets but also on employees’ psychological conditions that support long-term performance. This study aims to examine the effect of employee wellbeing on employee performance, with employee engagement as a mediating variable. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires from 150 employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that employee wellbeing has a positive effect on employee engagement and employee performance. Employee engagement also has a positive effect on employee performance. Furthermore, employee engagement partially mediates the relationship between employee wellbeing and employee performance. These findings highlight that employee wellbeing influences performance not only directly but also indirectly through enhanced work engagement as a key psychological mechanism. This study suggests that sustainable performance improvement strategies should emphasize the integrated management of employee wellbeing and engagement.